Effect of cold atmospheric plasma on common oral pathogenic microorganisms: a narrative review - Jiajun Xin; Hao Zhang; Yushen Li; Yifei Dai; Xiantao Chen; Jiatong Zou; Rui Wang; Zhihui Liu; Bowei Wang (Annals of Medicine)
Background The oral microbiota is a diverse and complex community that maintains a delicate balance. When this balance is disturbed, it can lead to acute and chronic infectious diseases such as dental caries and periodontitis, significantly affecting people’s quality of life. Developing a new antimicrobial strategy to deal with the increasing microbial variability and resistance is important. Cold atmospheric plasma (CAP), as the fourth state of matter, has gradually become a hot topic in the field of biomedicine due to its good antibacterial, anti-inflammatory, and anti-tumor capabilities. It is expected to become a major asset in the regulation of oral microbiota.Methods We conducted a search in PubMed, Medline, and Wiley databases, focusing on studies related to CAP and oral pathogenic microorganisms. We explored the biological effects of CAP and summarized the antimicrobial mechanisms behind it.Results Numerous articles have shown that CAP has a potent antimicrobial effect against common oral pathogens, including bacteria, fungi, and viruses, primarily due to the synergy of various factors, especially reactive oxygen and nitrogen species.Conclusions CAP is effective against various oral pathogenic microorganisms, and it is anticipated to offer a new approach to treating oral infectious diseases. The future objective is to precisely adjust the parameters of CAP to ensure safety and efficacy, and subsequently develop a comprehensive CAP treatment protocol. Achieving this objective is crucial for the clinical application of CAP, and further research is necessary.